Electro-optics handbook - Elion, Glenn R. (Electro-optics series, 1979)
In the Electro-Optics Handbook, authors perform a service to the entire profession by integrating previously scattered data into one up-to-date source that includes fundamental definitions and symbols; radiometric and photometric quantities; sources of radiation; lasers; detectors; image and camera tubes; optical formulae, materials, and components; human-electro-optics interaction; atmospheric and underwater transmittance; displays and arrays; communication systems; specialized components; and computer design of components and systems.